2000
DOI: 10.1016/s0735-1097(99)00535-5
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between angiotensin-I converting enzyme insertion/deletion polymorphism and response of plasma lipids and coronary atherosclerosis to treatment with fluvastatin

Abstract: Angiotensin-1 converting enzyme I/D polymorphism is associated with the response of plasma lipids and coronary atherosclerosis to treatment with fluvastatin. Subjects with DD genotype had a greater reduction in LDL-C, a higher rate of regression and a lower rate of progression of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 30 publications
4
36
1
Order By: Relevance
“…DNA preparation was as described previously. 18 TaqMan assays were obtained from ABI and used for all genotyping except for the CETP SNPs described previously. 16 The genetic effect of each polymorphism was evaluated using ANCOVA for each statin and for each clinical end point.…”
Section: Methodsmentioning
confidence: 99%
“…DNA preparation was as described previously. 18 TaqMan assays were obtained from ABI and used for all genotyping except for the CETP SNPs described previously. 16 The genetic effect of each polymorphism was evaluated using ANCOVA for each statin and for each clinical end point.…”
Section: Methodsmentioning
confidence: 99%
“…126 The Lipoprotein and Coronary Atherosclerosis Study demonstrated that subjects homozygous for the deletion (D) allele of the intron 6 insertion/deletion (I/D) polymorphism in the ACE gene exhibited a more favorable lipid response and angiographic regression of coronary atherosclerosis in response to treatment with fluvastatin. 127 In another study, homozygosity for the D allele of the ACE gene was associated with an improved antihypertensive response to ACE inhibitor therapy. 128 The I/D polymorphism also has been shown to influence blood pressure response to hydrochlorothiazide.…”
Section: Pharmacogenetics: Genetic Markers That Guide Therapeutic Strmentioning
confidence: 96%
“…An insertion/ deletion variant within the ACE gene has been reported to predict risk of recurring coronary events following statin treatment in several studies. [94][95][96] The IGTB3 gene encodes the platelet-specific fibrinogen receptor and variation in this gene has been associated under basal conditions with elevated risk of coronary disease. 94,97 This increase in risk was reported to be abolished by statin treatment.…”
mentioning
confidence: 99%